European cyclists' travel behavior: Differences and similarities between seven European (PASTA) cities. (June 2018) - Raser, Elisabeth; Gaupp-Berghausen, Mailin; Dons, Evi; Anaya-Boig, Esther; Avila-Palencia, Ione; Brand, Christian; Castro, Alberto; Clark, Anna; Eriksson, Ulf; Götschi, Thomas; Int Panis, Luc; Kahlmeier, Sonja; et al.
Abstract: While the annual number of trips of the average urban inhabitant has grown steadily in recent years, people are becoming less active while doing so. This lack of physical activity causes major health problems for individuals and great economic costs for society as a whole. Replacing short motorized trips by walking and cycling has been shown to increase physical activity in everyday life. The PASTA "Physical Activity through Sustainable Transport Approaches" project collected data in a longitudinal web-based survey with a cohort design to study the effects of active mobility on overall physical activity and health. An opportunistic sampling approach focusing on cyclists was applied to recruit more than 10000 participants in seven European cities, with half of them completing valid 1-day travel diaries at various time points. For this study, we compared 'cyclists' and 'non-cyclists' in terms of their overall travel behavior, physical activity and health. More than 2400 participants were identified as regular cyclists, 90% of which reached at least 30 min of active travel per day (the WHO´s recommended level) only by routine trips. When compared to non-cyclists, the share of women cycling regularly was lower; however, the share of people who had a driver's license and had at least sometimes access to a car was higher for regular cyclists. There were significant differences between cities in terms of cycling mode share, trip rates, trip duration and length, trip purpose and total physical activity, reflecting different geographical, economic, climatic and socio-cultural contexts. Our results indicate that cycling as a means of transport can help reach the WHO's physical activity recommendations. Highlights: Cyclists and non-cyclists travel behavior differ from each other. Cycling helps being active and reaching physical activity recommendations. In Cities with a high walking and PT share also non-cyclists are more active. Stakeholders can boost liveable cities by supporting walking and cycling measures.